ИННОВАЦИИ В ОБРАЗОВАНИИ: ПРОБЛЕМЫ ВНЕДРЕНИЯ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2018)
The article is devoted to the issues of innovation in education, concretely to the problem of its introduction. For understanding the essences of pedagogical innovations in education experts have two problems. The first of them is a problem of the study, generalization and spreading modern pedagogical technologies. The second problem concerns introducing the achievements of innovation projects in education in practice.
Keywords: innovation; pedagogics; studing process; methodology; teaching methods; creative activity